A Libras no ensino de leis de Newton em uma turma inclusiva de ensino médio - Cozendey, Sabrina Gomes (2013)
In the process called inclusion the regular schools gradually receive students with special needs, among these students there are someone who have a hearing limitation, those students can be identified as students with hearing disability or deaf. The educational process of students with deafness is characterized by uniqueness. As a consequence of this uniqueness, they require a different proposal work by offering a bilingual education, presume that the combined use of Portuguese written and Brazilian Sign Language (Libras). This work presents a discussion about the construction of a bilingual resource, the didactic bilingual, video that can be used in inclusive classrooms with students who have hearing disability. The object of the research study, the bilingual video, was also developed during the research. Are constructed six videos that emphasized some concepts of physics related to Newton's laws: speed, acceleration, resultant force, Newton's first law, Newton's second law and Newton's third law. The resource developed used the Brazilian sign language, the Portuguese language written and spoken, and dynamic images that represent everyday situations in which the concepts discussed can be observed. The resource analysis developed in the context of Physics inclusive education occurred aimed at evaluate the resource, checking if it was in fact a potential tool in inclusion promoting, and if the recourse favored the learning of physics concepts discussed. Participated in this research eighteen students the high school of public school localized in state of São Paulo. The videos were used at two different times (test 1 and test 2) in Physics inclusive class. To analyze the effectiveness of the resource developed were used questionnaires before and after the screening of videos and the proposed discussion. The results indicate that the recourse developed can be considered inclusive, because students with and without hearing disability could follow the lesson and learn the concepts discussed at the same time. The results also indicate that although many variables are present in an inclusive context, the use of a bilingual resource can make the class more inclusive.